Selective operation of three-level NPC inverter based on synchronous reference frame method supplying nonlinear loads in microgrid system - Mortezaei, A.; Simoes, M.; Durra, A.; Muyeen, S.M. (2016)
This paper develops selective strategies for Neutral Point Clamped Multilevel Inverter (NPC) in a microgrid application with load current decomposition based on Synchronous Reference Frame (DQ) method. The 3-level NPC inverter is investigated as widely used topology for medium and high power applications. In addition to the current injection into the grid, the 3-level NPC DG inverter is also being used to improve the power quality at point of common coupling, mitigating load current disturbances and improving power quality. For the islanded mode of operation, the control of the DG inverter involves the regulation of the instantaneous load line-to-neutral voltage magnitude, i.e. va, and frequency m. Single loop and multiloop voltage control scheme based on inductor filter current feedback are developed to regulate load voltage/frequency for a varity of load conditions. The control strategies are implemented in abc-frame. The principles supporting the selective control strategies are discussed and analyzed and the effectiveness of the control metod is demonstrated through digital simulations conducted by means of PSIM.